Analisis Kriteria Pelayan Tuhan yang Berkualitas Menurut 2 Timotius 1:6–8 dalam Konteks Tantangan Pelayanan di Era Postmodern - Priscilla F T Paay; Dennis Lesmana; Melki Solon (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the quality of a servant of God based on II Timothy 1:6–8 as a foundation for church development and spiritual growth. In reality, the role of God’s servant is often underestimated compared to other leadership roles in society, even though their quality greatly influences the life of the congregation and the direction of church ministry. The purpose of this research is to analyze the criteria for a quality servant of God in ministry, particularly in facing the challenges of the postmodern era, when relativism, individualism, and secularism often weaken spiritual commitment. The method used is a qualitative-analytical approach, with the primary data source being the biblical text of II Timothy 1:6–8, supported by secondary data obtained from theological literature, books, and relevant journal articles. Through exegesis and contextual analysis, this study identifies several essential criteria: the rekindling of spiritual gifts, the spirit of power, love, and self-discipline, as well as the courage to endure suffering for the sake of the Gospel. These characteristics are not only theological ideals but also practical demands for ministers who serve in a complex cultural and social environment. The findings of this study are expected to provide theoretical contributions to theological scholarship, particularly in the field of pastoral leadership and ecclesiology. In addition, the study offers practical guidance for church ministers in developing resilience, integrity, and Christ-centered leadership. The implication emphasizes that servant leadership rooted in character, love, obedience, and readiness to endure suffering is essential for strengthening faith, encouraging church growth, and glorifying God’s name. Therefore, the criteria outlined in II Timothy 1:6–8 remain highly relevant as a timeless foundation for effective ministry in the postmodern context